Islamic View On Secularism Through The Methodology Of Maudhu'i Interpretation - Risma Ayu Nursyahidah; Rofi Nugraha; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
This study investigates the genesis of secularism stemming from discontent with divine principles. It aims to delve into the Qur'anic perspective on secularism, employing a Tafsir Maudhu'iapproach. The qualitative methodology, utilizing descriptive techniques and library research, focuses on verses pertinent to secularism. Analysis reveals the Qur'an's implicit disapproval of secularism, evident in Surah Al-Hajj, verse 11, highlighting the consequences of separating worldly matters from religion. The findings underscore the inseparability of religious and worldly affairs, constituting an integral unity. This study emphasizes the interdependence between these realms, emphasizing that their detachment is untenable. It prompts reflection on the implications of secularization on religious beliefs and societal structures, challenging prevailing discourses on the division between religion and state. Ultimately, it contributes to a nuanced understanding of the intersection between religious teachings and contemporary governance paradigms.Furthermore, the study aims to contextualize its findings within the broader discourse on the relationship between religion and state in contemporary societies. By examining the implications of secularization on religious beliefs and societal structures, it seeks to shed light on the complexities of governance in pluralistic contexts. Through this nuanced exploration, the study not only challenges prevailing discourses but also offers insights into navigating the intersection between religious teachings and modern governance paradigms. Ultimately, it underscores the importance of fostering dialogue and understanding between religious and secular perspectives to promote social cohesion and inclusive governance frameworks. Thus, this study contributes to the ongoing conversation on the role of religion in shaping public life and informs efforts to create more equitable and harmonious societies